Molecular modeling in drug design - Wade, Rebecca C.; Salo-Ahen, Outi M. H. (Molecules, 2019)
This Special Issue contains thirteen articles that provide a vivid snapshot of the state-of-the-art of molecular modeling in drug design, illustrating recent advances and critically discussing important challenges [...]